Biophotonic composite scaffolds for controlled nitric oxide release upon NIR excitation - Ghanavati, S.; Magalhaes, E. Santos; Nguyen, C.; Bondzior, B.; Lastusaari, M.; Anker, J.N.; Draganski, A.; Petit, L.; Massera, J. (Elsevier BV, 2025)
For the first time, the preparation of 3D biophotonic scaffolds is reported. Scaffolds are prepared using the porogen burn-off technique and are capable of converting NIR to green emission, used to release nitric oxide from S-Nitroso-N-Acetylpenicillamine. NIR to green conversion is obtained by mixing CaWO4 crystals (codoped with Yb3+ and Er3+) with bioactive borosilicate glass prior to the sintering process. The scaffold fabrication process has a detrimental impact on the upconversion properties of the crystals embedded in the porous scaffold due to the formation of internal/surface crystalline defects and surface chemical bonds in the crystals. Nonetheless, we demonstrate that the brightness of the green emission, under 980 nm pumping, is sufficient to release nitric oxide from the scaffold covered with S-Nitroso-N-Acetylpenicillamine. Addition of upconverter crystals, in the bioactive scaffold, has no impact on porosity, mechanical properties, reactivity in simulated body fluid nor cytocompatibility. The progressive dissolution of the scaffold, associated with the precipitation of a reactive layer (HA), has no noticeable influence on the green emission under 980 nm pumping, showing that the development of such biophotonic scaffolds opens the path to light actuated drug release in a spatial–temporal manner, in vivo. Degradation of the up-converter particles does not lead to differences in cells viability.